Elite coaches have a similar prevalence of depressive symptoms to the general population and lower rates than elite athletes. Issue 1 (29th March 2020) - Kim, Simon Sang Yeob; Hamiliton, Bruce; Beable, Sarah; Cavadino, Alana; Fulcher, Mark L
Abstract : Objective: The primary aim of this study was to estimate the prevalence of depressive symptoms and life stress in elite coaches. The secondary aim was to explore the associations of depressive symptoms and life stress with demographic and lifestyle variables. Methods: National-level coaches were invited to participate in an online survey. Depressive symptoms were measured by the Centre for Epidemiological Studies Depression Scale-Revised (CESD-R). Life stress was measured using daily life hassle frequency and severity scores calculated from the Daily Hassles Questionnaire, with associations evaluated using linear regression. Results: Of 110 potential participants, 69 completed and two partially completed surveys were received. The majority of respondents were male (77%), coaching individual sports (70%) and aged under 50 (71%). Overall, 14% of coaches reported at least moderate depressive symptoms according to the CESD-R. Those contemplating retirement were more likely to show depressive symptoms. Reported life stress was higher in females and in those contemplating retirement. There was a strong association between life stress and the odds of experiencing depressive symptoms (p=0.006). Conclusions: Depressive symptoms are as prevalent in elite coaches as in general population, with potential risk factors including high levels of life stress and impending retirement.